A Scoring System to Stratify Curability after Endoscopic Submucosal Dissection for Early Gastric Cancer: "eCura system". (June 2017) - Hatta, Waku; Gotoda, Takuji; Oyama, Tsuneo; Kawata, Noboru; Takahashi, Akiko; Yoshifuku, Yoshikazu; Hoteya, Shu; Nakagawa, Masahiro; Hirano, Masaaki; Esaki, Mitsuru; Matsuda, Mitsuru; Ohnita, Ken; et al.
Abstract : Objectives: Although radical surgery is recommended for patients not meeting the curative criteria for endoscopic submucosal dissection (ESD) of early gastric cancer (EGC) because of the potential risk of lymph node metastasis (LNM), this recommendation may be overestimated and excessive. We aimed to establish a simple scoring system for decision making after ESD. Methods: This multicenter retrospective study consisted of two stages. First, the risk‐scoring system for LNM was developed using multivariate logistic regression analysis in 1, 101 patients who underwent radical surgery after having failed to meet the curative criteria for ESD of EGC. Next, the system was internally validated by survival analysis in another 905 patients who also did not meet the criteria and did not receive additional treatment after ESD. Results: In the development stage, based on accordant regression coefficients, five risk factors for LNM were weighted with point values: three points for lymphatic invasion and 1 point each for tumor size >30 mm, positive vertical margin, venous invasion, and submucosal invasion ≥500 μm. Then, the patients were categorized into three LNM risk groups: low (0–1 point: 2.5% risk), intermediate (2–4 points: 6.7%), and high (5–7 points: 22.7%). In the validation stage, cancer‐specific survival differed significantly among these groups (99.6, 96.0, and 90.1%, respectively, at 5 years; P <0.001). The C statistic of the system for cancer‐specific mortality was 0.78. Conclusions: This scoring system predicted cancer‐specific survival in patients who did not meet the curative criteria after ESD for EGC. ESD without additional treatment may be an acceptable option for patients at low risk.